纯电动物流车动力系统设计与优化 - 王永鼎; 李恒 (Jixie qiangdu)
In order to reasonably match the parameters of the electric logistics vehicle power system,according to the technical requirements of the electric logistics vehicle,the preliminary design and calculation of the relevant parameters of the electric logistics vehicle are carried out,and the whole vehicle simulation model is built by AVL-Cruise on the basis of the simulation conditions.Based on the complexity of parameter matching of pure electric logistics vehicle power system,various parameters need to be considered comprehensively,and a multi-objective genetic algorithm optimization method is proposed.The optimization method takes the vehicle’s power and economy as the optimization goal at the same time,and takes the maximum vehicle speed and acceleration time as constraints,establishes the transmission system optimization model and finds its optimal solution.Through the simulation analysis of the optimized parameters,the feasibility and rationality of the multi-objective genetic algorithm for the optimization of the power system of the electric logistics vehicle is presented,which provides a new way for the optimization of the power system parameters of the electric logistics vehicle.